2004
DOI: 10.1103/physreve.69.066119
|View full text |Cite
|
Sign up to set email alerts
|

Effective temperature in nonequilibrium steady states of Langevin systems with a tilted periodic potential

Abstract: We theoretically study Langevin systems with a tilted periodic potential. It is known that the ratio Theta of the diffusion constant D to the differential mobility mu(d) is not equal to the temperature of the environment (multiplied by the Boltzmann constant), except in the linear response regime, where the fluctuation dissipation theorem holds. In order to elucidate the physical meaning of Theta far from equilibrium, we analyze a modulated system with a slowly varying potential. We derive a large scale descri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 13 publications
2
81
0
Order By: Relevance
“…[42,14,41,25,23,44]. For such systems, we show a modified fluctuation-dissipation theorem (MFDT) that may be written in the form…”
Section: Introductionmentioning
confidence: 99%
“…[42,14,41,25,23,44]. For such systems, we show a modified fluctuation-dissipation theorem (MFDT) that may be written in the form…”
Section: Introductionmentioning
confidence: 99%
“…This is essentially a consequence of detailed balance and the role of the partition function as a moment-generating function, and thus such relations cannot be readily extended to nonequilibrium steady states. However, it has recently been shown that certain FDRs can be extended to far-from equilibrium steady states by use of an effective temperature [43,44]. Here we will therefore consider whether the nonequilibrium susceptibility and the scaled variance of the dynamic order parameter can be related aŝ…”
Section: Applicability Of a Fluctuation-dissipation Relationmentioning
confidence: 99%
“…(1) is not necessarily fulfilled out of equilibrium and violations are observed in a variety of systems such as glassy materials [1,2,3,4,5], granular matter [6], and biophysical systems [7]. This motivated a theoretical work devoted to a search of a general framework describing FD relations, see the review [8] or [9,10,11,12,13,14] for recent attempts in simple stochastic systems. In the same spirit, a modified fluctuation-dissipation theorem (MFDT) has been recently formulated for a non-equilibrium steady dynamics governed by the Langevin equation with nonconservative forces [15].…”
mentioning
confidence: 99%